Baitul Hikmah as Intellectual Pillar: Social Studies of Islamic Education in Baghdad on Sustaining the Glory of the Abbasids - Ririn Ristiani; Amelia Mona Sari; Ellya Roza (JEICI - Journal of Education and Islamic Contemporary Issue, 2026)
This study examines the role of Baitul Hikmah as an intellectual pillar in the social history of Islamic education in Baghdad during the heyday of the Abbasid Dynasty. Baitul Hikmah functions as a translation center, academy, and library, serving as the epicenter of scientific development. The full support of the Abbasid caliphs, especially Al-Ma'mun, enabled an inclusive and multicultural scientific tradition that included Muslim and non-Muslim scientists. The research method used is a literature study with a historical-qualitative approach. With primary and secondary sources from historical works on Islamic civilization and scientific articles. The study's results show that Baitul Hikmah not only advanced science but also fostered a critical, open, and transformative scientific culture, thereby sustaining the political, social, and intellectual glory of the Abbasid Dynasty. This study makes an important contribution to understanding how Islamic education in the past laid the foundation for the emergence of advanced civilization and offers inspiration for the development of contemporary Islamic education.